2021
DOI: 10.1101/2021.05.26.445908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage-Derived Depolymerase as an Antibiotic Adjuvant Against Multidrug-Resistant Acinetobacter Baumannii

Abstract: Bacteriophage-encoded depolymerases are responsible for degrading capsular polysaccharides (CPS), lipopolysaccharides (LPS) and exopolysachcharides (EPS) of the host bacteria during phage invasion. They have been considered as promising antivirulence agents in controlling bacterial infections, including those caused by drug-resistant bacteria. This feature inspires a hope of utilizing these enzymes to disarm the polysaccharide capsid of the bacterial cells, which then strengthens the action of antibiotics. Her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Recent studies have shed light on the potential of combining depolymerases with other compounds. Chen et al (2021) identified during a trial, a depolymerase Dpo71 from an A. baumannii phage in the heterologous host E. coli to combat multidrug-resistant A. baumannii . The team concluded after further research that Dpo71 presented the ability to enhance antibiotic activity, specifically colistin, and demonstrated that at 10 μg/ml, Dpo71 enabled a total eradication of human serum bacteria at 50% volume ratio.…”
Section: How Phages Combat Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shed light on the potential of combining depolymerases with other compounds. Chen et al (2021) identified during a trial, a depolymerase Dpo71 from an A. baumannii phage in the heterologous host E. coli to combat multidrug-resistant A. baumannii . The team concluded after further research that Dpo71 presented the ability to enhance antibiotic activity, specifically colistin, and demonstrated that at 10 μg/ml, Dpo71 enabled a total eradication of human serum bacteria at 50% volume ratio.…”
Section: How Phages Combat Biofilmmentioning
confidence: 99%
“…Dpo71 was also able to inhibit both existing as well as new biofilm formation. Chen et al further proposed that the potential combination therapy of Dpo71 with colistin could enhance antibiofilm capabilities, therefore, increasing the survival rate of infected patients ( Chen et al, 2021 ). A further list of recent combination therapy is demonstrated in Table 4 .…”
Section: How Phages Combat Biofilmmentioning
confidence: 99%
“…Combining antibiotics with phagederived enzymes such as lysins, holins or depolymerases, can also boost the antimicrobial effect and significantly constrain resistance [15]. A depolymerase specific to Acinetobacter baumannii in addition to antibiotics, decreased bacterial population sizes, treatment-resistance frequency and biofilm formation in vitro [16]. Resistance frequency in bacteria against these phagederived proteins had never previously been recorded [17].…”
Section: Minimizing Phage-resistance Evolutionmentioning
confidence: 99%